Sirolimus in Refractory Cronkhite-Canada Syndrome and Focus on Standard Treatment - Catherine Langevin MD; Hugo Chapdelaine MD; Jean-Maxime Picard MD; Pierre Poitras MD; Raymond Leduc MD, FRCPC (SAGE Publishing, 2018)
Cronkhite-Canada syndrome is a rare syndrome consisting of extensive gastrointestinal polyposis and ectodermal changes including cutaneous hyperpigmentation, alopecia, and onychodystrophy. We report the case of a 45-year-old Caucasian male patient who failed multiple treatments over 2 years including steroids, azathioprine, adalimumab, and cyclosporine. He had recurrent and prolonged hospitalizations because of diarrhea, abdominal pain, weight loss, and malnutrition. Sirolimus was initiated with a significant clinical and endoscopic benefit apparent within, respectively, 2 and 8 weeks. An ongoing remission was achieved and maintained for over 6 months after prednisone tapering. We review the current evidence on treatment of Cronkhite-Canada syndrome and suggest the incorporation of sirolimus in that algorithm.